THE CORRELATION BETWEEN STUDY HABITS AND LEARNING OUTCOMES IN MATHEMATICS OF FOURTH GRADE STUDENTS OF ELEMENTARY SCHOOL - maryah, helvi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
This research is to find out the correlation which positive and significant between study habits with learning outcomes in mathematics of fourth grade students in model school No. 02, Bukittinggi. This research used quantitative approach with correlation research design. The research population consist of 102 students with 81 students as the research sample. The sampling technique used is a propotional random sampling. Collection methods are a study habits questionnaire and learning outcomes in mathematics documentation. Analysis prerequisite test used normality and linearity. Hypotheses testing used Pearson Product Moment with sig.5%. The result showed that the study habits and learning outcomes in mathematics are categorized as moderate. The hypotheses test results also showed the  r-value bigger than the r-table value, with  0,820 > 0,218. Thus, it is concluded  that there is a positive and significant correlation between study habits with learning outcomes in mathematics.